ANALISIS SEKTOR UNGGULAN KABUPATEN BUTON UTARA - Feby Febrianti Yusuf; Wali Aya Rumbia; Muhammad Nur Afiat (Universitas Halu Oleo, 2019)
The problems discussed in this study are what sectors are superior in North Buton Regency. The purpose of this research is to find out what sectors are superior in the current North Buton Regency by looking at the GRDP growth in 2013-2017. The data obtained in the analysis uses Location Quotient analysis.Based on the Location Quotient analysis which includes the base sector is the sector of agriculture, forestry, fisheries, the Construction Sector sector; Large and retail trade sectors; car and motorcycle repair; Real estate sector; The government administration, defense, and social security sectors are mandatory; and the health services sector and social activities. The agricultural sector is a leading sector in North Buton Regency, which contributes the most to the North Buton Regency GRDP. Even though its contribution continued to decline throughout the year but its absolute value continued to increase. In addition to the agricultural sector, North Buton GRDP is supported more by the Construction and Trade Sector. Although its contribution has not changed much in forming the North Buton Regency GRDP, both of these sectors are base sectors that have competitive advantages and specialization in the North Buton Regency region.